ДӘСТАН ДӨРЕТИЎ ДӘСТҮРИ ҲӘМ «ҚЫРЫҚ ҚЫЗ» - Алламбергенов, К. (SCIENCE and SOCIETY, 2021)
The presentation presents the origin of “Kyryk kiz/Fourty gilrs” dastan, as an unique national folk masterpiece of Karakalpak people. This claim came after analysis of origin, development and evolution of dastan by individual authors and dzhiraw’s presenting style were investigated widely based on above mentioned principles.
Keywords: heroic epic poem; epic genesis of dastan; «Womanizing country» fairytale; «Gulayim» fairytale; social and solo masterpiece; principles of dastan (epic-poem) creating; national attributes of dastan: national language; regional territory; national psychological image; national traditions; national life-style; relationship with neighboring countries; contribution of dzhiraw in national dastan presenting; «kyryk kiz/Fourty girls» -unique dastan of Karakalpak folk